Graphic-Semantic Expression Map: A New Approach in Design Teaching Methodologies - Rijo, Cátia (2020)
This paper aims to contribute to the discussion in design teaching and its consequent research context, considering participatory practices and methodologies. In the context of curricular units related to design and teaching experience, the problematic question arises: in the teaching of graphic design, what methodologies and instruments can we apply that associate semantics with visual thinking? This problem led to the need to better-evaluate the methodological instruments currently used and to perceive the feasibility of readapting them in order to overcome the difficulties experienced. Based on the traditional concept map, we create a graphicsemantic expressions map that intends to make the relationship between the various evaluable elements more understandable.